Fraudulent Financial Statements Detection Using Fraud Triangle Analysis: Institutional Ownership as A Moderating Variable - Indah Anisykurlillah; Muhammad Noor Ardiansah; Afifah Nurrahmasari (Accounting Analysis Journal, 2022)
Purpose : The study investigates the empirical evidence of financial targets, financial stability, external pressure, the nature of the industry, and rationalization’s influence on financial statement fraud, with institutional ownership as a moderating variable. Method : The population’s study included 58 publicly listed companies on the Indonesia Stock Exchange and formed the LQ45 in 2016–2018. Purposive sampling was used on 29 companies, and descriptive and regression analyses were performed using SPSS. Findings : The results showed that financial targets have a positive effect on financial statement fraud, and the industry’s nature has a negative effect on financial statement fraud. In contrast, financial stability, external pressure, and rationalization do not implicate financial statement fraud. In addition, institutional ownership could undermine the effect of financial targets on financial statement fraud. Still, it could affect financial stability, external pressure, industry nature, or rationalization of financial statement fraud. Users of financial statements concentrate on the level of corporate profit because the extent of manipulation indicates that. Novelty : The research initiates an initial study that examines the engagement of institutional ownership as a moderating variable because it not only increases but also risks the possibility of fraud in the financial statements, which reflect financial performance. Keywords : Fraud Financial Statement; Fraud Triangle; Institutional Ownership